THE ASSESSMENT OF THE SPIROGYRA VARIANS AND CHARA VULGARIS COMPARATIVE AND COMBINED ANTIOXIDANT POTENTIAL (Journal of Medical & Health Sciences Review, 2025)
Oxidative stress (OS) is a common mechanism of tissue destruction in vivo that has been implicated in the origin and impact of numerous diseases. The rising incidence of cancer can now be explained in two ways: first, by environmental contaminants; and second, by lifestyle choices including smoking, drinking, and eating. Chara vulgaris is a sophisticated kind of algae that is also known as sand grass, skunkweed, or stonewort. Alkaloids, steroids, flavonoids, tannins, and terpenoids are among the substances that Spirogyra varians produce. According to reports, Spirogyra neglecta (SN) has anti-inflammatory, antidiabetic, and antioxidant properties. We found the antioxidant potential of Spirogyra varians using DPPH free radical assay 15.2%, 26%, 33%. We observed the antioxidant potential of Chara vulgaris 23%, 35%, and 43%. Furthermore, we next examined the combined antioxidant potential of Spirogyra varians and Chara vulgaris. We found that the 23%, 41%, and 53%. Our results suggest that the combined antioxidant potential of Spirogyra varians and Chara vulgaris is more significant than the individual ones. Further, an in vivo approach is needed to clarify the mechanism of the combined antioxidant potential of both Spirogyra varians and Chara vulgaris.